Summary of the Development of Belt Drives Industry - Shu'an Qin; Peng Zhou; Yujie Zhou; Hongyuan Jiang (Jixie chuandong)
Combining the development of internal and overseas belt drives industry， the time sequence of the evolution of the driving belt is sorted out， it mainly includes flat belt drives， V-belt drives， V-ribbed belt drives， synchronous belt drives and composite type belt drives. The academic research and technical standardization work in the field of belt drives in China are comprehensively introduced， the development trend of belt drives industry is analyzed， and the development direction of the industry is given.